Imaginário, poder e Estado o sujeito (sobre)vive - Giuliani Neto, Ricardo (Universidade do Vale do Rio do Sinos, 2007)
This dissertation intends to demonstrate that the Government as we know presently is a product of the capitalist economical system and arose in the XVII and XVIII centuries as product of a process of rationalization that has organized the exercise of the political power. The State of modernity is the surpass of the absolute Government in proportion that takes in its rationality the private exercise of the private property replacement of the property that one used to concentrate in the absolute and feudal Government. Their crisis is cyclical and permanent in proportion that operates as agents able to produce functionaries constitutions assuring, therefore, its survival while purposed-instrumental display. In this context, one finds the man as individual of socials changes. The engaged man that rationalizes to exerts concerns to execute concerns and that, thus, establishes the society in proportion that one empowers, to be created by it. The events of the politics, considered as the surrounding by excellence wh
Keywords: burguesia; Conélius Castoriadis; esfera pública; mídia; sistema capitalista; imaginário radical; bourgeoisie; capitalist system; Conélius Castoriadis; media; public sphere; radical imaginary; Ciências Sociais Aplicadas